PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA BUNDA PADANG - Suryanto, Dio - (Pendidikan Matematika, 2014)
The background of this research is about the students understanding of mathematical concepts is low and student responsibility, discipline and honesty to the tasks. It can be seen from the results of learning mathematics outcomes at XI class in SMA Bunda in academic year 2013/2014. The study is aimed to determine whether the type of active learning strategies with tournament learning type affects to the studentsâ understanding in mathematical concepts at XI class in SMA Bunda Padang and how the of students attitudes development in active learning by applying tournament learning type. The research is pre-experimental research, the research design of pre-test and post-test. The subjects are all students at XI class science in academic year 2014/2015 consisting of one class. Research instrument is a test of understanding of mathematical concepts and attitude assessment rubric. The test used is validated in narrative form by the teacher. The data analysis technique used is the t test. Based on the results of the hypothesis test values obtained t = 10.73367 and t0,025=2,052, because t > t0,025 the proposed hypothesis is accepted at the significance level Î± = 0.05. It can be concluded that active learning strategies application with tournament learning type of studentsâ understanding in mathematical concepts at XI class in SMA Bunda Padang and studentsâ attitudes at XI class science are becoming increasingly better.